Liquid spray characteristics in burner system: A short review - Amirnordin, Shahrin Hisham; Khalid, Amir; Tan Yan Hao (Research Progress in Mechanical and Manufacturing Engineering, 2020)
It is important to have a thorough understanding of the fluid flow and spray characteristics in air-assisted atomizers, since this will affect the efficiency of atomization and the performance of combustion. Previous researchers have established many factors that influenced the spray of many types of atomizers. This project reviews the main factors which can affect the spray characteristics of the atomizers. The main parameters considered are spray penetration, spray angles, spray droplets and spay break-up. The first part is analysis recaps the efficiency of the spray atomization can be enhanced by increasing the basic surface area of the liquid bulk to achieve high levels of evaporation. The air inlet geometry in the air assisted atomizer therefore plays a crucial role in improving the quality of the sprays. The second aspect is the length of the internal mixing chamber was varied to see the results of their atomisation. The nozzle efficiency was investigated, and the internal mixing chamber’s efficacy was discussed. The final section is the performance of the nozzle was investigated and the efficacy of an internal mixing chamber was discussed. The air and fluid flow levels were calculated in absolute from 170 kPa to 790 kPa under the air plenum condition. In addition, to test the spray characteristics, flow past nozzle and downstream was visualised. Though unstable flow near the critical condition of assisted-air pressure was observed, the nozzle showed steady flow beyond the critical condition. The results show that the efficiency was adequate for the present atomizer. In addition, the density of SMD and spray droplets is the highest in the center of the spray field and slowly decreases along the radial direction. The outcome of this work provides a better understanding of spray characteristics and its related parameter to the improvement of spray system in the future.